FORMULASI KONSEP MODERASI ISLAM BERBASIS KEINDONESIAAN DALAM MEREDUKSI RADIKALISME AGAMA DI INDONESIA (KAJIAN EPISTEMOLOGIS-HISTORIS) - M. Mucharom Syifa (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2019)
The religious phenomenon of Islam in post-reform Indonesia is thought to have experienced extremism and radicalism. The explosion of terrorism in the name of Islam that occurred between 1998 and 2018 made the face of Indonesian Islam in the world. Whereas in fact Islam in Indonesia is Islam that promotes moderate principles (tawassuth / washatiah) in preaching, namely taking a middle ground between the opposite two extreme poles. Da’wah method of Washatiyatul Islam or Moderation of Islam is a method of da’wah that emphasizes the Islamic values of Rahmatan Lil Alamin. Da’wah is friendly with tradition, so it can grow in a multicultural and multi-religious society. It is this characteristic of accommodative Islam that is the stronghold of the prevention of radical religious ideas. This article using the epistemological-historical-holisitic approach wants to explore the concept of moderation of Islam in the context of the Indonesian nation and the shallowness of religious reasoning. As a result, none of the strong references say that the spread of Islam in ancient Archipelago was by radical means. The history of Islam in the archipelago has struggled with diverse localities. Islam is not present to break down or chop away existing traditions and local culture, but try to dialect with the context in which Islam is located. Because of its flexible nature, Islam is able to survive and develop so that it raises a new Islamic style that is unique and does not exist in any part of the world.